Preparation of Fucoidan-Based Electrospun Nanofibers and Their Interaction With Endothelial Cells - Chen, Yiwen; Zhu, Huilin; Hao, Yuanping; Sun, Zhanyi; Shen, Peili; Zhou, Qihui (Frontiers in Bioengineering and Biotechnology, 2021)
Sulfated polysaccharide fucoidan (FD) is widely applied in biomedical applications owing to its outstanding bioactivities. In addition to the biochemical features, the architecture of biomaterials plays a critical role in tissue repair and regeneration. Particularly, nanofibers have elicited great interest due to their extracellular matrix-like structure, high specific surface area, and favorable biological properties. Herein, chitosan-modified FD/ultra-high molecular weight polyethylene oxide (UHMWPEO) nanofibers are developed via green electrospinning and electrostatic interaction for studying their interaction with endothelial cells. The appropriate solvent is screened to dissolve FD. The electrospinnability of FD/UHMWPEO aqueous solutions is greatly dependent on the weight ratios of FD/UHMWPEO. The incorporation of UHMWPEO significantly improves the electrospinnability of solution and thermo-stability of nanofibers. Also, it is found that there is good miscibility or no phase separation in FD/UHMWPEO solutions. In vitro biological experiments show that the chitosan-modified FD/UHMWPEO nanofibers greatly facilitate the adhesion of endothelial cells and inhibit the attachment of monocytes. Thus, the designed FD-based nanofibers are promising bio-scaffolds in building tissue-engineered blood vessels.